(untitled) (Third Sector Social Economic Review, 2017)
Rapid developments in communication technology have provided various opportunities for businesses. Improvements in technology enable businesses to interact with consumers through social Networks. Today businesses use applications that allow consumers to organize via Internet and smart phones in order to gain competitive advantage through catching up with demand changes. Gamification that enables consumers to organize regardless of time and place has recently become widespread all around the world as well as Turkey. Even the number of studies concerning the gamification and consumer behavior has been increasing recently, it can be said there is still limited studies in this area. The main purpose of this study is to determine whether attitude towards the gamification and word of mouth intentions of Turkish consumersdiffers in terms of gender and income level. Research conducted on the active users of Foursquare and Swarm- the applications that perform with game instruments for consumers to find out new places- that widely accepted as two of the most common examples of gamification. Data was collected through online survey. Survey prepared on Google docs conducted on 234 consumers who actively use the Foursquare/Swarm. In accordance with the objective of the research, Mann Whitney U test conducted. Results revealed that attitude towards gamification and WOM intentions of Turkish consumers regarding gamification do not differs both in terms of gender and income level.